Combination of Dexmedetomidine and Tramadol in Patient-Controlled Intravenous Analgesia Strengthens Sedative Effect in Pregnancy-Induced Hypertension - Zhang, Shu-Yao; Zhao, Hui; Xu, Chengcheng; Zhang, Qiuzhen; Chen, Yun; Li, Hai-Yan; Zhang, Xia-Lan; Zhao, Chengkuan; Chen, Meini; Yang, Dong-Hua (Frontiers in Pharmacology, 2021)
Objective: The aim of the present study is to explore the combination of dexmedetomidine (DXM) and tramadol (TMD) on sedative effect in patients with pregnancy-induced hypertension (PIH). Methods: A total of 356 patients with pregnancy-induced hypertension (PIH) were randomly divided into three groups: DXM, TMD and DXM + TMD groups. These patients were treated with different doses of DXM, TMD or combination of DXM and TMD by a patient-controlled intravenous injection device. The scores of static pain and dynamic pain, sedation degree, and adverse reaction were recorded. The plasma levels of inflammatory mediators IL-10 and C-reactive protein (CRP), and the serum level of p-p38-MAPK were evaluated. Results: It was found that administration with DXM 1.0 µg/kg/h + TMD 700 mg and DXM 2.0 µg/kg/h + TMD 600 mg result in stronger sedative effect than single administration with DXM or TMD. The mean arterial pressure (MAP) and heart rate (HR) of patients with PIH were decreased with the combinational treatment of DXM and TMD. Interestingly, the PIH patients injected with DXM 1.0 µg/kg/h + TMD 700 mg and DXM 2.0 µg/kg/h + TMD 600 mg showed stronger sedative effect. In addition, the plasma level of level of IL-10 was increased and CRP decreased. The serum level of p-p38/MAPK was decreased. Conclusion: Taken together, our study indicates that combination of DXM and TMD effectively lowers blood pressure and reduces inflammation through increasing the level of IL-10, reducing CRP and inhibiting p-p38/MAPK in patients with PIH. This study suggests that the combination of DXM and TMD could be an anesthetic choice in the management of PIH.